Review of global burden of disease studies: trends, challenges, and future directions - Otorkpa, Oche Joseph; Otorkpa, Chinenye Oche; Emmanuel, Stephen; Olaiya, Abiodun Paul; Auta, Helen Shnada; Daniel, Ebenezer Obi; Adebola, Onifade Adefunmilola; Ojodale, Paul Isaac (International Journal of Public Health Science (IJPHS), 2024)
Global burden of disease (GBD) studies plays an important role in assessing the variability of risk factors, injuries, and diseases worldwide, providing essential evidence for policy-making and healthcare planning. This study presents a review of current literature on GBD studies, aiming to analyze the trends, challenges, and future directions in this field. We conducted a review of published GBD studies from inception to date, utilizing major scientific databases and relevant sources. Our findings reveal several noteworthy trends in GBD studies. Over the years, GBD studies have expanded to cover a wider range of diseases and risk factors, providing a more comprehensive understanding of global health. Advances in data availability, technology, and modeling techniques have improved the accuracy of disease burden estimates. The inclusion of disability-adjusted life years (DALYs) has enabled comparisons as well as prioritization of interventions. However, challenges remain, such as limited data in middle and low-income countries and methodological complexities. The COVID-19 pandemic has emphasized the need for responsive methodologies. Future directions include strengthening data collection, utilizing machine learning, big data analytics, ethical use of artificial intelligence and promoting collaboration for consistent GBD studies.